Pengaruh Konsentrasi Sorbitol dan Variasi Tingkat Penyangraian Terhadak Karakteristik Fisikokimia dan Organoleptik Kopi Robusta Cililin - Thomas Gozali; Ikrawan, Yusep; Maulana Ghaffar, Rizal; Nurul, Gianita; Muhammad Ramadhan, Rizal (Jurnal Penelitian Pertanian Terapan, 2024)
Cililin is one of the robusta coffee producing regions in Indonesia, but there are still many people who do not know robusta coffee from Cililin, so an effort is needed to improve its quality. Coffee that goes through heating stages such as drying or roasting will cause several other chemical ingredients to change. Coffee processing can affect the characteristics and taste of the coffee produced. Soaking with sorbitol solution can retain moisture (humectant) in food and in processing that undergoes high temperature treatment so that it will not cause browning reactions One of the stages carried out in coffee processing using high temperatures is the roasting process. Therefore, a study was conducted to determine the effect of the difference in sorbitol concentration with roasting level on the characteristics of the Cililin robusta coffee products produced. This study consisted of two factors, namely sorbitol concentration (a1=10%, a2=15%, a3=20%) and roasting rate (b1 = Light Roast, b2 = Medium Roast, b3 = Dark Roast).Data processing using Two Way Anova on SPSS application version 26.0. The results showed that concentration had an effect on water content, color test and organoleptic response in color, aroma, and texture attributes, but did not affect the characteristics of caffeine levels, and pH. Roasting rate affects coffee characteristics, namely moisture content, caffeine content, pH, color test, and organoleptic response in color, aroma, and texture attributes. The interaction between sorbitol concentration and roasting rate affects the characteristics of robusta cililin coffee, namely moisture content and color test. However, it has no effect on the characteristics of caffeine levels, and pH.